Analisis City Branding Kabupaten Sukoharjo Sebagai Kota Jamu: Pendekatan Persepsi Brand Box Model - Lilik Wahyudi; Sarjiyanto Sarjiyanto; Pram Suryanadi (University of Merdeka Malang, 2019)
This study aims to assess the model city branding based on superior product through perception approach of brand box models. This study is conducted to explore consumer perceptions of a traditional medicinal herbal drink products”jamu” in order to build a city branding by medicinal product as region superior product as part of the local communities empowerment. Development of city branding is conducted by the exploration of perception approach of brand box models. Exploration of perception is conducted by ethnographic methods and netnographic methods in several target areas of research. The area regions of this research are Soloraya region (subosukowonosraten) as the market potential of a city branding Sukoharjo. This results show : 1) there is a strong influence of the perception of the city image on overall value; 2) there is the strong influence of overall value on the intention to recommend and intention to visit https://doi.org/10.26905/jmdk.v7i1.2688